Atomistic Simulation of Temperature-Dependent Interfacial Diffusion between Solid Nickel and Liquid Aluminum - Alzais Safii; Yoyok Winardi; Sudarno; Desriyanti; Norhasnidawani Johari; Ali Selamat; Rizal Arifin (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
The performance and durability of welded joints are directly influenced by interfacial diffusion between the metals involved, making it essential to investigate the effect of temperature on these processes. The present research examines temperature-dependent diffusion mechanisms at the interface between solid nickel and liquid aluminum using molecular dynamics simulations. Investigations were conducted at 1200, 1300, 1400, and 1500 K to explore the influence of temperature on atomic mobility and interfacial mixing. Radial distribution function analysis revealed a significant increase in the diffusion of nickel atoms into the aluminum phase with increasing temperature, indicating enhanced atomic interactions at the interface. The mean square displacement analysis supported these findings, showing that aluminum atoms were more mobile than nickel atoms at lower temperatures, while nickel atoms exhibited a faster diffusion rate with increasing temperature, surpassing aluminum in mobility. This trend is reflected in the diffusion coefficients, which exhibit a temperature-dependent increase in the diffusion rate of the nickel atoms. These results emphasize the role of temperature in controlling the diffusion dynamics at the solid–liquid interface. The insights gained from this study are critical for optimizing processes, such as dissimilar metal welding, where precise control over interfacial diffusion is essential for achieving the desired material properties and ensuring the structural integrity of nickel–aluminum joints in high-temperature applications.